The gut dysbiosis-cancer axis: illuminating novel insights and implications for clinical practice - Asseri, Amer H.; Bakhsh, Tahani; Abuzahrah, Samah Sulaiman; Ali, Sajad; Rather, Irfan A. (Frontiers in Pharmacology, 2023)
The human intestinal microbiota, also known as the gut microbiota, comprises more than 100 trillion organisms, mainly bacteria. This number exceeds the host body cells by a factor of ten. The gastrointestinal tract, which houses 60-80% of the host's immune cells, is one of the largest immune organs. It maintains systemic immune homeostasis in the face of constant bacterial challenges. The gut microbiota has evolved with the host, and its symbiotic state with the host's gut epithelium is a testament to this co-evolution. However, certain microbial subpopulations may expand during pathological interventions, disrupting the delicate species-level microbial equilibrium and triggering inflammation and tumorigenesis. This review highlights the impact of gut microbiota dysbiosis on the development and progression of certain types of cancers and discusses the potential for developing new therapeutic strategies against cancer by manipulating the gut microbiota. By interacting with the host microbiota, we may be able to enhance the effectiveness of anticancer therapies and open new avenues for improving patient outcomes.